(untitled) (Journal of Parents and Teachers, 2014)
Fourteenth article of the “music and more music” series, dedicated to Punk music style. A brief explanation of this style is carried out, focusing on its history, social environment, musical characteristics and more common themes. After this introduction, a song is suggested and worked in classroom, doing a brief analyze of the lyrics and the music. Lastly, a series of activities are shown, which are oriented to work different values in classroom. The proposed song in this article is “21st Century Breakdown”, by Green Day Group. The worked values in this song are the recognition of the importance of historical knowledge, social commitment and self-knowledge.